Precipitation Variations in the Flood Seasons of 1910–2019 in Hunan and Its Association With the PDO, AMO, and ENSO - Zeng, Yuxing; Huang, Chao; Tang, Yihao; Peng, Jiadong (Frontiers in Earth Science, 2021)
Floods in the middle reaches of the Yangtze River threaten thousands of million people, causing casualties and economic loss. Yet, the prediction of floods in this region is still challenging. To better understand the floods in this region, we investigate the interdecadal-interannual rainfall variation of the flood season (April–September) in Hunan province. The relationship between the rainfall and the Pacific decadal oscillation (PDO), Atlantic Multidecadal Oscillation (AMO), and El Niño-Southern Oscillation (ENSO) are also analyzed. The results show that the precipitation in the flood seasons shows an interdecadal oscillation with a period of about 20 years, which is caused by the joint effect of the PDO and AMO. When the PDO and AMO are in the same phase, the corresponding flood season is characterized by more precipitation, and conversely, it is less precipitation. Further analyses show that in the year after El Niño, when the PDO and AMO are both in the positive phase, it is favorable for the west Pacific subtropical high (WPSH) to be stronger and more southward than normal. Such circulation anomaly is conducive to the water vapor transport to the southern China, and as a result there is more precipitation in Hunan. When the PDO and AMO are both in the negative phase, the WPSH is weaker than normal, but the India-Burma trough is obviously stronger, which is also favorable for the southwesterly water vapor transport to the southern China. However, in the next year of the La Niña year, regardless of the phase combination of the PDO and AMO, the southern coast of China are controlled by a negative geopotential height anomaly and the WPSH retreats to the sea, which is not conducive to the northward transport of water vapor, and the precipitation in Hunan is less than normal. But if only the cold SST background in the previous stage is considered (without reaching the standard of a La Niña event),is more precipitation in most of the Hunan Province. Therefore, at the interannual scale, the PDO and AMO also have a modulating effect on the precipitation signal. However, the interannual-scale ENSO signal has a greater influence on the precipitation in Hunan flood seasons. Our results will give implications for the predications of floods in Hunan.